Analysis of Factors Affecting Employee Job Satisfaction After Workplace Relocation: A Systematic Literature Riview - Shinta Hanifah; Mohammad Wartaka, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The purpose of this study is to systematically identify journal articles related to workplace relocation and employee job satisfaction by analyzing the factors that influence employee job satisfaction after workplace relocation with four research questions that have been made, including variable identification, research topics, factors that influence employee job satisfaction after a workplace relocation, and research methods. This study was conducted using the Systematic Literature Review (SLR) method by reviewing 52 journal articles related to workplace relocation sourced from Google Scholar and Scopus. The results show that there are 39 journal articles were studies that used the variable “satisfaction” as the variable affected by the variable “relocation” in their research. 36% of research topics from relevant journal articles discuss relocation and its impacts. There are 24 factors that influence employee job satisfaction after workplace relocation, with qualitative research methods being the most common. From a practical perspective, this research will provide guidance for companies in planning and implementing workplace relocation by considering factors that have been shown to influence employee job satisfaction. From a theoretical perspective, this study strengthens our understanding of the relationship between workplace relocation and various aspects of job satisfaction and offers an opportunity to develop more specialized theories on human resource management. Although previous studies often discuss relocation in terms of performance, productivity, and organizational efficiency, no one has systematically analyzed how workplace relocation impacts employee job satisfaction.